Inheritance Rights of Extramarital-Children after the Constitutional Court Decision of 2010 - Lestari, Putri Wartina; Judiasih, Sonny Dewi; Nugroho, Bambang Daru (Universitas Muhammadiyah Yogyakarta, 2023)
Extramarital-children refer to children who are born outside the marriage. The position extramarital-children are legally vulnerable and therefore needs attention. The Constitutional Court Decision No. 46/PUU- VIII/2010 recognizes the legal status of extramarital children against their biological fathers as long as their genetic relationship can be proven by way of DNA testing and supported with other evidence. This study aims to examine the inheritance right of the extramarital-children, especially after the issuance of the mentioned Constitutional Court Decision. This normative legal research employs statutory, case and comparative approaches. Although the focus of this study is more on the legal development in Indonesia, however, this paper also provides a comparative analysis with some other countries, especially with regard to the utilization of the DNA Testing for legal purposes. The results show that the Constitutional Court Decision No. 46/PUU-VII/2020 does not address the inheritance right of extramarital-children and therefore they cannot inherit each other from their biological fathers. In regard to inheritance, this issue will be referred to the existing law of inheritance.